News, Emotions, and Policy Views on Immigration - Elena Manzoni; Elie Murard; Simone Quercia; Sara Tonini (Institute of Labor Economics (IZA), 2024)
How do emotions affect policy views on immigration? How do they influence the way people process and respond to factual information? We address these questions using a survey experiment in Italy, which randomly exposes around 7,000 participants to (i) sensational news about immigrant crimes, (ii) statistical information about immigration, or to (iii) the combination of both. First, we find different effects of news depending on the severity of the reported crime: while the news of a rape against a young woman significantly increases the demand for anti-immigration policies, there is no impact of the news of a petty theft. Consistent with a causal role of emotions, we find that the rape news triggers a stronger emotional reaction than the theft news, while having a similar effect on factual beliefs. Second, we document that information provision corrects beliefs, irrespective of whether participants are also exposed to the rape news. Yet, the exposure to the rape news strongly influences whether belief updating translates into change in policy views: when presented in isolation, information tends to reduce anti-immigration views; when combined with the rape news, the impact of the latter dominates and participants increase their anti-immigration views to the same extent as when exposed to the rape news only. This evidence suggests that, once negative emotions are triggered, having more accurate factual knowledge no longer matters for forming policy views on immigration.
Keywords: F22; C90; D91; D72; D83; J15; 330; news; information; immigration; experiment; belief; emotions